Aspek Hukum Praktik Penghapusan Akun Pengguna Sistem Elektronik Secara Sepihak untuk Memoderasi Konten Oleh Marketplace Menurut Peraturan Menteri Komunikasi dan Informatika Nomor 5 Tahun 2020 tentang Penyelenggara Sistem Elektronik Lingkup Privat - Tiara Bastari Putri; Sinta Dewi; Enni Soerjati Priowirjanto (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
The aim of this research is to analyze legal aspects of the practice of unilaterally deleting electronic system user accounts to moderate content by the marketplace according to the regulation of the minister of communication and informatics number 5 of 2020 concerning electronic system organizers scope. This research was conducted using a normative and comparative juridical approach method with research specifications, namely analytical descriptive. Data collection techniques are carried out through literature studies and online data searches as well as examining laws and regulations and books, journals, and other references relevant to the research. The results of this study indicate that the Minister of Communication Regulation Number 5 of 2020 concerning Private Scope Electronic System Operators has not implemented all marketplace obligations as stated in previous regulations. This has led to violations of several marketplace obligations which have resulted in not maximizing the implementation of content moderation practices. In relation to protection efforts for electronic system users, a legal framework is needed that can further specify and regulate obligations, limits of responsibility, and transparency to provide a more adequate protection function for electronic system users.